Subtract 2x to get an expression for y

2x + y = 4

y = 4 - 2x

Now, use each of your values of x to find the corresponding value of y

y = 4 - 2(-5) = 4 + 10 = 14. The first point is (-5, 14).

Y = 4 - 2(0) = 4. The second point is (0, 4).

Y = 4 - 2(1) = 4 - 2 = 2. The third point is (1, 2).

2x + y = 4

y = 4 - 2x

Now, use each of your values of x to find the corresponding value of y

y = 4 - 2(-5) = 4 + 10 = 14. The first point is (-5, 14).

Y = 4 - 2(0) = 4. The second point is (0, 4).

Y = 4 - 2(1) = 4 - 2 = 2. The third point is (1, 2).